The time course of the lower threshold of motion during rapid events of adaptation - Barraza, Jose Fernando (2001)
To examine how the time course of rapid events of adaptation affect motion vision, the lower threshold of motion (LTM) was measured for suprathreshold sinusoidal gratings in presence of transient and steady glare. In the case of the transient condition, glare and stimulus were presented separated in time by a variable extent (SOA: 50–450 ms). A two alternative forced choice paradigm using the method of constant stimuli was adopted to measure the LTM. It was found that LTM follows the characteristic Crawford’s time course of adaptation. Results are similar for two stimulus duration (300 and 500 ms). It was proposed that the increment of contrast threshold for displacing gratings (Ctq) due to the loss of sensitivity produced by the sudden onset of the glare source can explain the results.